Word Matching Game: An Interactive Media to Vocabulary Learning - Ayuni, Erin Windi; Rohbiah, Tatu Siti; Amalia, Ila (Journal of English Language Teaching and Cultural Studies, 2025)
This research aimed to determine the effect of using a word matching game on students’ vocabulary mastery of eighth grade students at one public junior high school in Serang City. The method used in this study was a quasi-experiment involving two classes as research subjects. After the data collection process was completed, the researcher conducted data analysis using the t-test to test the significance of the research results. The results showed that the average pre-test score in the experimental class was 60.33 which increased to 70.67 in the post-test. On the other hand. the average pre-test score in the control class was 57.50 with an increase to 62.17 in the post-test. Statistical analysis showed that the t-count value (2.411) was greater than the t-table value at the 5% (1.672) and 1% (2.392) significance levels. Based on these results, the null hypothesis (Ho) was rejected while the alternative hypothesis (Ha) was accepted. Thus, it can be concluded that the word matching game is proven to be effective in enhancing students' vocabulary mastery.